A specialized training program enhances university students’ knowledge, attitudes, and practices on volunteering: evidence from Oman - Farouk Saleh, Emad; Al-Maamari, Wafa Said; Ibrahim, Ahmed Thabet Helal; Mostafa, Magdy M.; Padma Sri Lekha, P.; Abdul Azeez, E. P. (Frontiers in Sociology, 2025)
The decreasing involvement of youth in voluntary practices necessitates training and mobilizing them for voluntary activities. Therefore, the present study aimed to develop and test the efficacy of a culture-sensitive training program on enhancing knowledge, attitude, and practice (KAP) of volunteering among university students in Oman. We adopted a quasi-experimental design with a pre-post-test on the KAP of volunteering and designed a specialized training program spanning 10 weeks. Training was given to two groups of university students independently during different semesters to test the efficacy of the program (group 1 and group 2). The results of the paired t-test suggested a significant difference in knowledge, attitude, practice, and overall KAP [group 1: t(29) = 15.73, p < 0.01; group 2: t(59) = 7.18, p < 0.01] in the pre-post-tests in both groups, pointing to the good efficacy of the program. Cohen’s d indicates a significant effect size for the KAP of volunteering in both groups. The results emphasize the relevance of mobilizing students for volunteering by enhancing their awareness and practice of volunteering. We recommend adding this training program as part of extra-curricular activities in academic institutions across Oman and similar contexts. Facilitating voluntarism among university students has implications for contributing to Sustainable Development Goals (SDGs) through education for sustainable development efforts envisaged in targets 4.7 and 17.7.